PENGARUH SUBSTITUSI TEPUNG UBI JALAR UNGU (IPOMOEA BATATAS L.) TERHADAP SIFAT FISIKOKIMIA DAN SENSORIS NASTAR: The Effect Of Purple Sweet Potato Flour (Ipomoea batatas L.) Substitution On Physicochemical And Sensory Properties Of Nastar Cookies - Jazirotur Rizqiyah; Mohammad Jusuf Randi; Abdul Bashar (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2026)
The purpose of this study was to assess the physicochemical and sensory characteristics of cookies (nastar) using purple sweet potato flour (Ipomoea batatas L.) as a partial substitute for wheat flour. The experiment used a one-factor Completely Randomized Design (CRD) with four substitution levels of purple sweet potato flour, namely 0%, 20%, 30%, and 40%, each conducted in triplicate. Parameters analyzed in this study included color (L, a, b), anthocyanin content, moisture content, shelf life, and sensory characteristics. Analysis of variance (ANOVA) and Duncan's test were used to assess the data at a 5% significance level. Increasing the proportion of purple sweet potato flour substitution resulted in lower lightness (L) and b values, indicating a darker product color, while the a value ranged from 12.57 to 14.68. The amount of anthocyanin increased dramatically from 1.89 ppm to 8.51 ppm. Moisture content varied from 6.76 to 7.39% and did not differ significantly between treatments (p>0.05), although it increased to 8.70% on the 28th day of storage. Sensory evaluation showed a significant impact on aroma (p<0.05), but color, texture, and flavor were not significantly affected (p>0.05). In conclusion, because purple sweet potato flour increases anthocyanin content without significantly reducing consumer acceptance, this flour can be used as a partial substitute for wheat flour in nastar cookies.